EFFETS DU STRESS ABIOTIQUE SUR LES ÉCOSYSTEMES AQUATIQUES - Amel,SIOUANE; Naassima,ARGOUB (My University, 2020)
Although our work, consists of a bibliographical synthesis, it dealt with a subject of abiotic stress in plants, which is a topical subject and of continuous importance, hence the impact of stress remains a challenge for researchers in the field of ecology and agronomy... ػهى انسغم مه أن ػمهىب يتكىن مه تىنيف ببهيىغسافي ، إال أوه تؼبمم مغ مىضىع اإلجهبد انالأحيبئي في انىببتبث ، وهى مىضىع مىضؼي وذو أهميت مستمسة حيث يظم تأثيس اإلجهبد يمثم تحديًب نهببحثيه في هرا انمجبل. مجبل ػهم انبيئت وانهىدست انززاػيت................... Malgré que notre travail consiste à une synthèse bibliographique, il a traité un sujet de stress abiotique chez les plantes, qui est un sujet d'actualité et d'importance continue d'où l'impact de stress reste un défi aux chercheurs dans le domaine d'écologie et d’agronomie.